Introgression of an adult-plant powdery mildew resistance gene Pm4VL from Dasypyrum villosum chromosome 4V into bread wheat - Wei, Yi; Zhang, Ting; Jin, Yinyu; Li, Wen; Kong, Lingna; Liu, Xiaoxue; Xing, Liping; Cao, Aizhong; Zhang, Ruiqi (Frontiers in Plant Science, 2024)
Powdery mildew caused by Blumeria graminis f. sp. tritici (Bgt) seriously threatens wheat production worldwide. Dasypyrum villosum (2n = 2x = 14, VV) is a relative of wheat and harbors novel genes for resistance against multi-fungal diseases. In the present study, we developed a complete set of new wheat-D. villosum disomic introgression lines by molecular cytogenetic methods. This set included four disomic substitution lines (2n=42) containing respectively chromosomes 1V#6, 2V#6, 3V#6, and 6V#6, and four disomic addition lines (2n=44) containing respectively chromosomes 4V#6, 5V#6, 6V#6 and 7V#6. These lines were subsequently evaluated for their responses to a mixture Bgt isolates at both seedling and adult-plant stages. Among them, the introgressed introgression lines containing chromosomes 3V#6, 5V#6, and 6V#6 showed resistance at both seedling and adult-plant stages. In addition, only the chromosome 4V#6 disomic addition line NAU4V#6-1 exhibited a high level of adult plant resistance to powdery mildew. Through genomic in situ hybridization (GISH), fluorescence in situ hybridization (FISH) and 4V#6-specific markers analysis, two translocation lines were further developed from the progenies of NAU4V#6-1 and the Ph1b mutation line NAU0686-ph1b. They were T4DL• 4V#6S translocation line NAU4V#6-2 and T7DL• 7DS-4V#6L translocation line NAU4V#6-3.Powdery mildew tests of these lines confirmed the presence of an adult-plant powdery mildew resistance gene, Pm4VL, located on the terminal segment of chromosome arm 4V#6L. In comparison with the recurrent parent NAU0686 plants, the T7DL• 7DS-4V#6L translocation line NAU4V#6-3 showed no obvious negative effect on yield-related traits, providing a new germplasm in breeding for resistance.